Porphyromonas gingivalis induces an inflammatory response via the cGAS-STING signaling pathway in a periodontitis mouse model - Bi, Rong; Yang, Yanling; Liao, Hongwei; Ji, Guang; Ma, Yan; Cai, Lukui; Li, Jingyan; Yang, Jingsi; Sun, Mingbo; Liang, Jiangli; Shi, Li (Frontiers in Microbiology, 2023)
Periodontal disease is an inflammatory disease caused by oral bacteria, that eventually leads to alveolar bone destruction as inflammation persists. However, the chronic periodontitis pathological relevance of Porphyromonas gingivalis (P. gingivalis) infection, particularly in the inflammatory response, remains largely unknown. Understanding the stimulation of the inflammatory response by P. gingivalis opens a new approach to host modulation therapies in periodontology. Herein, we investigated whether P. gingivalis infection triggers type I IFN gene and various cytokine expression and leads to activation of the cGAMP synthase–stimulator of IFN genes (cGAS-STING) pathway both in vitro and in a mouse model. Additionally, inflammatory cytokines act on osteoblasts and the receptor activator of nuclear factor-κB ligand (RANKL)-producing cells, resulting in osteoclast differentiation and activation. In an experimental model of periodontitis with P. gingivalis, StingGt mice showed lower levels of inflammatory cytokines and bone resorption than wild-type mice. Furthermore, we report that a STING inhibitor (SN-011) significantly decreased inflammatory cytokine production and osteoclast formation in a periodontitis mouse model with P. gingivalis. In addition, STING agonist (SR-717) -treated periodontitis mice displayed enhanced macrophage infiltration and M1 macrophage polarization in periodontal lesions compared with vehicle-treated periodontitis mice. In conclusion, our results demonstrate that the cGAS-STING signaling pathway may be one of the key mechanisms crucial for the P. gingivalis-induced subsequent inflammatory response leading to chronic periodontitis.